Laboratory IR spectroscopy of soils from Apollo 14, 15, and 16: Spectral parameters and maturity. (15th November 2022) - Morlok, A.; Joy, K.H.; Martin, D.; Wogelius, R.; Hiesinger, H.
Abstract: Sieved size fractions (0–25 ​μm, 25–63 ​μm, 63–125 ​μm, and 125–250 ​μm) and bulk (unsieved) material from lunar soils from Apollo 14 (14163, 135 and14259, 672), Apollo 15 (15101, 319 and 15401, 147), and 16 (61220, 41, 62231, 55 and 67481, 96) were analyzed in diffuse reflectance in the mid-infrared (3–18 ​μm). These soils reflect formation in a range of geological settings including basalt protoliths (Apollo 15), and feldspathic impact ejecta protoliths (Apollo 14 and Apollo 16). Mid-IR spectra analyses were made with the same samples using broad spot analyses using a diffuse reflectance set up, and by micro-FTIR under low vacuum and ambient laboratory conditions. Comparison of the data generated by the Broad Spot and micro-FTIR Techniques shows only minor differences in terms of both band positions and relative intensities. Aims were to investigate the mid-infrared reflectance features of the Apollo soils, extract and compare spectral parameters with varying sample composition. Results show a general similarity of the mid-IR spectra with spectral bands indicating the presence of the mineral anorthite, a glassy/amorphous component and a weak contribution from pyroxene. Furthermore, we have investigated the effects of space weathering to the soils, all of which have different maturity indices (from immature, to submature, and mature). This indicator could, thus, provide an easy, non-destructive technique for future laboratory studies of space weathering of airless planetary body soils. Highlights: Mid-infrared reflectance spectra of Apollo soils were obtained. Samples from Apollo 14, 15 and 16 were studied. Comparison of broad spot and micro-FTIR techniques show similar results. An indicator for soil maturity was investigated.